2020
DOI: 10.46858/vimsjpt.2108
|View full text |Cite
|
Sign up to set email alerts
|

Peak Expiratory Flow Rate in Sedentary Population: An Observational Study

Abstract: Background- To date there are very few studies evaluating the relationship between sedentary behaviour and pulmonary function in a population who works for more than half a day i.e. 6-8hrs continuously in front of technologies (mainly desk jobs) with no sign of physical activities. Hence the aim of the study was to evaluate the effects of a sedentary lifestyle on peak expiratory flow rate. METHOD- The study was conducted on 75 desk job workers, males and females of age group 30-45 years working for 6-8 hours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…NSP is usually illustrated as an alternative technique of breathing through the nostrils (Sengupta, 2012). Several studies involving NSP practices affirm the benefits observed in autonomic brain and cardiovascular functions, pulmonary disorders, and blood pressure (Dhanvijay and Chandan, 2018;Shah and Kothari, 2019). Shah and Kothari (2019) report in their study that NSP is effective in tranquilizing the stressful mind.…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…NSP is usually illustrated as an alternative technique of breathing through the nostrils (Sengupta, 2012). Several studies involving NSP practices affirm the benefits observed in autonomic brain and cardiovascular functions, pulmonary disorders, and blood pressure (Dhanvijay and Chandan, 2018;Shah and Kothari, 2019). Shah and Kothari (2019) report in their study that NSP is effective in tranquilizing the stressful mind.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Several studies involving NSP practices affirm the benefits observed in autonomic brain and cardiovascular functions, pulmonary disorders, and blood pressure (Dhanvijay and Chandan, 2018;Shah and Kothari, 2019). Shah and Kothari (2019) report in their study that NSP is effective in tranquilizing the stressful mind. In another study by Gupta et al (2014) the authors found out ameliorations in problem solving skills of the participants.…”
Section: Literature Reviewmentioning
confidence: 88%
“…The simplicity of the method is in its main advantage .It is measured by using a standard Wright Peak Flow meter .Peak flow measurement which measures the speed at which air is exhaled from our lungs ,giving a measurement of how well your airways are working . Peak expiratory flow is measured in units of liters per minute (13) . Post COVID-19 syndrome can heavily affect the health related quality of life .Physical life and quality of life are directly related factors.…”
Section: Introductionmentioning
confidence: 99%